Upaya Meningkatkan Hasil Belajar PPKn Materi Hakekat Dan Teori Kedaulatan Melalui Pendekatan Saintifik Berbantuan Puzzle Peta Konsep Pada Siswa Kelas 9A SMP Negeri 13 Magelang - Zaetun, Zaetun (Faculty Of Education, 2024)
This research is classroom action research (PTK). Each cycle consists of three stages of activity, namely planning, implementing actions and observing, and reflecting. The subjects of this research were students in class 9 A of SMPN 13 Magelang City with a total of 30 students. Data collection in this research used teacher and student activity observation sheets as well as written tests. The data analysis technique used is descriptive qualitative and descriptive quantitative with percentages. The results of the research show that the level of PPKn learning outcomes on the Nature and Theory of Sovereignty in class 9A students at SMPN 13 Magelang after implementing learning using a scientific approach assisted by Concept Map Puzzles in cycle I was an average of 76.6 after being carried out in cycle II the average was 84. Behavioral changes that occurred in class 9A students at SMPN 13 Magelang in implementing learning using a scientific approach assisted by Concept Map Puzzles to improve PPKn learning outcomes on the Nature and Theory of Sovereignty include the following (a) students are more able to be independent (b) students are more active ( c) students are more able to work together and take responsibility and (d) students are able to create / arrange Concept Map Puzzles correctly.